Disease‐biased and shared characteristics of the immunoglobulin gene repertoires in marginal zone B cell lymphoproliferations. Issue 4 (30th January 2019) - Xochelli, Aliki; Bikos, Vasilis; Polychronidou, Eleftheria; Galigalidou, Chrysi; Agathangelidis, Andreas; Charlotte, Frédéric; Moschonas, Panagiotis; Davis, Zadie; Colombo, Monica; Roumelioti, Maria; Sutton, Lesley‐Ann; Groenen, Patricia; et al.
Abstract: The B cell receptor immunoglobulin (Ig) gene repertoires of marginal zone (MZ) lymphoproliferations were analyzed in order to obtain insight into their ontogenetic relationships. Our cohort included cases with MZ lymphomas ( n = 488), i.e. splenic (SMZL), nodal (NMZL) and extranodal (ENMZL), as well as provisional entities ( n = 76), according to the WHO classification. The most striking Ig gene repertoire skewing was observed in SMZL. However, restrictions were also identified in all other MZ lymphomas studied, particularly ENMZL, with significantly different Ig gene distributions depending on the primary site of involvement. Cross‐entity comparisons of the MZ Ig sequence dataset with a large dataset of Ig sequences (MZ‐related or not; n = 65 837) revealed four major clusters of cases sharing homologous ('public') heavy variable complementarity‐determining region 3. These clusters included rearrangements from SMZL, ENMZL (gastric, salivary gland, ocular adnexa), chronic lymphocytic leukemia, but also rheumatoid factors and non‐malignant splenic MZ cells. In conclusion, different MZ lymphomas display biased immunogenetic signatures indicating distinct antigen exposure histories. The existence of rare public stereotypes raises the intriguing possibility that common, pathogen‐triggered, immune‐mediated mechanisms may result in diverse B lymphoproliferations due to targeting versatile progenitor B cells and/or operating in particular microenvironments. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.